SERVICE CULTURE - Nakrob Narksuwan, นักรบ นาคสุวรรณ์ (Dusit Thani College Journal, 2018)
Service culture is the construction of a model of organizational services with an aim to provide quality and satisfactory services to customers to ensure customer satisfactions and loyalty which impact the image and revenue of the organization. The concept of service culture construction includes setting goals, seeking supporters, making the model understood among the employees, arranging trainings and practices, implementing the model in authentic situations, evaluating the outcome, and announcing the model as the organizational policy. After fully implementing the service model, it must be monitored and improved continuously to ensure the model can be applied smoothly and contemporarily. Feedback from related parties should be obtained for further evaluation and development. If positive feedback is obtained, the service culture model can be transferred to the next operators and become one of the organizational cultures.